2009
DOI: 10.1074/jbc.m807498200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sphingosine Kinase by Bovine Viral Diarrhea Virus NS3 Is Crucial for Efficient Viral Replication and Cytopathogenesis

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid implicated in diverse cellular functions including survival, proliferation, tumorigenesis, inflammation, and immunity. Sphingosine kinase (SphK) contributes to these functions by converting sphingosine to S1P. We report here that the nonstructural protein NS3 from bovine viral diarrhea virus (BVDV), a close relative of hepatitis C virus (HCV), binds to and inhibits the catalytic activity of SphK1 independently of its serine protease activity, whereas HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 36 publications
2
64
2
Order By: Relevance
“…Recently, SK2 has been shown to increase the replication of some hepatitis C virus strains by interfering with oxidative stress and lipid peroxidation in infected cells (Yamane et al, 2014). The above studies linking high levels of SK with enhancement of viral infection are in contrast to our own observations of a reduction in SK1 activity in response to dengue virus (DENV) infection (Wati et al, 2011), as also reported for the related flavivirus bovine viral diarrhea virus (Yamane et al, 2009). Close analysis of the time-course of the reduction in SK1 in DENV-infected cells demonstrates a correlation with high levels of the DENV 39 UTR, which can compete for the SK1 activator eEF1A (Carr et al, 2013a;Leclercq et al, 2008Leclercq et al, , 2011, which is utilized by flaviviruses to assist replication (Blackwell & Brinton, 1997;Davis et al, 2007).…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Recently, SK2 has been shown to increase the replication of some hepatitis C virus strains by interfering with oxidative stress and lipid peroxidation in infected cells (Yamane et al, 2014). The above studies linking high levels of SK with enhancement of viral infection are in contrast to our own observations of a reduction in SK1 activity in response to dengue virus (DENV) infection (Wati et al, 2011), as also reported for the related flavivirus bovine viral diarrhea virus (Yamane et al, 2009). Close analysis of the time-course of the reduction in SK1 in DENV-infected cells demonstrates a correlation with high levels of the DENV 39 UTR, which can compete for the SK1 activator eEF1A (Carr et al, 2013a;Leclercq et al, 2008Leclercq et al, , 2011, which is utilized by flaviviruses to assist replication (Blackwell & Brinton, 1997;Davis et al, 2007).…”
Section: Introductioncontrasting
confidence: 55%
“…Close analysis of the time-course of the reduction in SK1 in DENV-infected cells demonstrates a correlation with high levels of the DENV 39 UTR, which can compete for the SK1 activator eEF1A (Carr et al, 2013a;Leclercq et al, 2008Leclercq et al, , 2011, which is utilized by flaviviruses to assist replication (Blackwell & Brinton, 1997;Davis et al, 2007). Additionally, our previous data (Carr et al, 2013a;Calvert et al, 2015), as well as that of Yamane et al (2009), suggest an increase in SK1 activity in the early hours following infection. Thus the roles of SK1 in viral infection may vary in relation to the time post-infection (p.i.…”
Section: Introductionmentioning
confidence: 99%
“…Studies used the yeast-two hybrid (Y2H) screening system to screen individual BVDV proteins for host binding partners ( demonstrated that NS3 from BVDV binds to and inhibits the catalytic activity of sphingosine kinase 1 (SphK1). NS3-SphK1 binding enhance BVDV replication and BVDVinduced apoptosis (Yamane et al 2009a). Using Y2H screening, the subunit of bovine translation elongation factor 1A (eEF1A) was shown to interact with the NS5A polypeptide of BVDV (Johnson et al 2001).…”
Section: Virus-host Interacting Partnersmentioning
confidence: 99%
“…Goat anti-mouse IgG1, IgG2a or anti-rabbit IgG, IgG1 antibodies conjugated with Alexa 488, Alexa 594, Alexa 568 or Alexa 488, respectively, were from Invitrogen. Protein concentrations in samples were determined with a Protein Quantification kitRapid using BSA as a standard as described previously (Yamane et al, 2009a;Zahoor et al, 2009). Recombinant NS5A was used as an antigen to generate mouse mAb and its specificity was verified by ELISA, immunoprecipitation, immunoblot and immunofluorescence as described previously (Zahoor et al, 2009).…”
mentioning
confidence: 99%